2017
DOI: 10.1186/s12944-017-0416-7
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy, safety, Low density lipoprotein cholesterol lowering, and calculated 10-year cardiovascular risk reduction of alirocumab and evolocumab in addition to maximal tolerated cholesterol lowering therapy: a post-commercialization study

Abstract: BackgroundEfficacy and safety of proprotein convertase subtilisin-kexin type 9 (PCSK9) inhibitors, alirocumab (ALI) and evolocumab (EVO) have previously been evaluated through controlled clinical trials with selective patient groups. Post-commercially, in patients with heterozygous familial hypercholesterolemia (HeFH) and/or cardiovascular disease (CVD) with suboptimal LDL cholesterol (LDLC) lowering on maximal tolerated cholesterol lowering therapy, we assessed efficacy and safety of ALI and EVO.MethodsPost-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 43 publications
(84 reference statements)
1
8
0
Order By: Relevance
“…But this effect is not significant with Ezetimibe. 24 LDL reduction is attained at 4 weeks and remains considerably constant through 12 and 24 weeks, 25 and this is consistent with the study done by Shahawy et al 13 which showed constant LDL reduction for upto 2 years. LDL reduction is shown to be accompanied by percent and absolute decrease in calculated 10 year cardiovascular risk calculated by both ACC/AHA and NIH calculators.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…But this effect is not significant with Ezetimibe. 24 LDL reduction is attained at 4 weeks and remains considerably constant through 12 and 24 weeks, 25 and this is consistent with the study done by Shahawy et al 13 which showed constant LDL reduction for upto 2 years. LDL reduction is shown to be accompanied by percent and absolute decrease in calculated 10 year cardiovascular risk calculated by both ACC/AHA and NIH calculators.…”
Section: Discussionsupporting
confidence: 86%
“…LDL reduction is shown to be accompanied by percent and absolute decrease in calculated 10 year cardiovascular risk calculated by both ACC/AHA and NIH calculators. 25 In statin intolerance, Ezetimibe is the recommended alternative to statins but causes only 15-20% of LDL reduction. 26 In the absence of statins, a higher magnitude of LDL reduction is required and this need can be addressed by Alirocumab.…”
Section: Discussionmentioning
confidence: 99%
“…We previously carried out an open label efficacy and safety 24-week study of ALI and EVO in 72 patients with HeFH and/or CVD with suboptimal LDL cholesterol (LDLC) lowering on maximal tolerated cholesterol lowering therapy [ 21 ]. Post-commercially, we started 25 patients on ALI 75 mg, 15 on ALI 150 mg, and 32 on EVO 140 mg every 2 weeks added to a maximally tolerated entry LDLC lowering regimen, with follow-up for a median 24 weeks.…”
Section: Introductionmentioning
confidence: 99%
“…At 24 weeks, on ALI 75 mg, median LDLC decreased from 117 to 62 mg/dL (−54%), on ALI 150 mg, LDLC fell from 175 to 57 mg/dL (−63%), and on EVO 140 mg, LDLC fell from 165 to 69 mg/dL (−63%), p < 0.0001 for all. Absolute and percent LDLC reduction did not differ ( p > .05) between ALI 150 and EVO 140 mg, but were less on ALI 75 mg vs ALI 150 mg and EVO 140 mg ( p < .05) [ 21 ]. Percent reductions in 10-year CVD risks by AHA and NIH calculators, respectively were ALI 75 mg −22% and −44%, ALI 150 mg −31% and −50%, and EVO 140 mg −29% and −56%, p ≤.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation